A Morphometric analysis of cervical spondylotic myelopathy pathoanatomy : correlation between magnetic resonance imaging findings and clinical presentation - Hishamudin bin Din (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
Introduction: Cervical spondylotic myelopathy (CSM) is the most common cause of spinal cord dysfunction in modern society worldwide. Magnetic resonance imaging (MRI) remains the imaging modality of choice for CSM. However, MRI findings are not completely specific for clinically significant CSM. Aim: This cross-sectional study aimed to determine the pathoanatomy of CSM patients and analyze the correlation between clinical special tests and MRI findings Materials and Methods: Patients aged 30 to 80 years old diagnosed to have CSM from a single tertiary hospital with no previous cervical spine disease or injuries were be recruited for the study. Clinical parameters include specific clinical sign and other clinical key features.. MRI findings analyzed include level of compression, specific underlying degenerative pathology, and parameters for cord compression. Results: Thirty patients were recruited and reviewed. Commonest myelopathic sign observed in majority of them (60%) were positive Hoffmann's sign and presence of reverse brachioradialis reflex. All patients have either degenerative or prolapse disc changes on MRI. 90% of them showed evidence of osteophyte formation, 36.7 % with facet hypertrophy changes at least at one level and 23.3% had thickening or infolding ligamentum flavum. None were identified with ossification of posterior longitudinal ligament (OPLL) or lamina hypertrophy. Myelopathic hand signs and other specific clinical signs noted significantly correlated with the cervical cord compression and significantly observed in patients with smaller cord diameter. There is a positive correlation between the clinical key features with MRI parameters for canal and cord diameter. The transverse cord diameter, cord compression ratio and approximate cord area were shown to be the only independent variable related to almost all of the positive clinical specific tests. All three have moderate to strong correlation with the clinical findings. These correlations reflect compression of the cord indicating cord compression play a major role in the pathophysiology of CSM. It is suggested that these measurements are sensitive indicators of canal stenosis. Conclusion: MRI parameter such as canal and cord size of cervical spine is an objective reﬂection of compression on spinal cord, and it is associated with cervical spinal cord function. It may play a signiﬁcant role in predicting the severity and outcome of CSM